Randomized clinical trial of psychological support and sleep adjuvant measures for postoperative sleep disturbance in patients undergoing oesophagectomy. Issue 10 (14th July 2017) - Scarpa, M.; Pinto, E.; Saraceni, E.; Cavallin, F.; Parotto, M.; Alfieri, R.; Nardi, M. T.; Marchi, M. R.; Cagol, M.; Castoro, C.; ,
Abstract : Background: Major surgery such as oesophagectomy requires a postoperative stay in intensive care. Painful stimuli lead to sleep disturbance and impairment in quality of life. The aim of this study was to evaluate the effect of psychological counselling and sleep adjuvant measures on postoperative quality of sleep and quality of life. Methods: This RCT was performed between January 2013 and October 2015. Patients undergoing oesophagectomy for cancer were randomized into one of four groups receiving: psychological counselling plus sleep adjuvant measures during the ICU stay; psychological counselling alone; sleep adjuvant measures alone during the ICU stay; or standard care. The primary endpoint was impairment in quality of life measured using the European Organisation for Research and Treatment of Cancer C30‐QL2 questionnaire between admission for surgery and discharge from hospital. The secondary endpoint was impairment in quality of sleep assessed by means of the Pittsburgh Sleep Quality Index between admission for surgery and hospital discharge. Results: The local ethics committee approved the early termination of the study because of relevant changes in the ICU setting. Some 87 patients were randomized and 74 patients were evaluated in the analysis. Psychological counselling reduced the impairment in quality of life (odds ratio 0·23, 95 per cent c.i. 0·09 to 0·61) and in quality of sleep (odds ratio 0·27, 0·10 to 0·73). Conclusion: Perioperative psychological support reduces impairment in quality of life and quality of sleep after oesophagectomy. Registration number: NCT01738620 (http://www.clinicaltrials.gov ). Abstract : Psychologists improve postoperative sleep